Optimalisasi Parameter Proses Mesin CNC Milling Terhadap Kekasaran Permukaan Yang Akan Digunakan Untuk Membuat Cetakan Kampas Rem Depan - Fadel Ramiro; Eko Yudo; Sukanto Sukanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to determine the optimal parameters in the CNC Milling process to produce low surface roughness and improve the quality of brake pad molds. By applying the Taguchi method, the results showed that the process parameters have a significant effect on surface roughness. Data analysis revealed that increasing feed speed and depth were positively correlated with surface roughness. Of the parameters tested, feed speed had the largest contribution of 40.46%, followed by feed depth of 14.01%, and spindle speed of 12.36%. The optimal parameter combination proposed to achieve the best surface roughness is a feed speed of 100 mm/min, a feed depth of 0.2 millimeters, and a spindle rotation of 3343 RPM. These findings provide an important contribution to the automotive industry to improve the efficiency and quality of brake pad production, a component that plays a crucial role in vehicle safety.